Capital Controls or Real Exchange Rate Policy? A Pecuniary Externality Perspective - Gianluca Benigno; Huigang Chen; Christopher Otrok; Alessandro Rebucci; Eric Young (Inter-American Development Bank (IDB), 2013)
In the aftermath of the global financial crisis, a new policy paradigm has emerged in which old-fashioned policies such as capital controls and other government distortions have become part of the standard policy tool kit (so called macro- prudential policies). On the wave of this seemingly unanimous policy consensus, a new strand of theoretical literature contends that capital controls are welfare enhancing and can be justified rigorously because of second-best considerations. Within the same theoretical framework adopted in this fast-growing literature, this paper shows that a credible commitment to support the exchange rate in crisis times always welfare-dominates prudential capital controls, as it can achieve unconstrained allocation.
Keywords: E52; F37; F41; 330